Processing digital ink input subject to monitoring and intervention by an application program - Tu, Xiao; Sun, Yibo; Menon, Krishnan; Durojaiye, Olumuyiwa; Weins, Connor (2018)
A facility for processing ink input is described. In one example facility, the facility receives ink input from an input device. The facility generates and renders ink stroke data structures in response to received ink input in accordance with an ink input processing pipeline. The facility provides to an executing application access to information traversing the ink input processing pipeline at a selected point in the ink input processing pipeline.